Photocatalytic water purification from phenol and formaldehyde - Ivantsova, Natalya A.; Kuzin, Evgeniy N.; Churina, Alina A. (Известия Саратовского университета. Новая серия: Серия Химия. Биология. Экология, 2022)
Industrial development leads to an increasing number of persistent and highly toxic organic compounds such as phenol and formaldehyde. Chemical oxidation processes (in particular, photooxidation) are widely used for water treatment and wastewater and groundwater treatment. As part of the work done, an assessment of the possibility of using photocatalysis for post-treatment of wastewater from phenol, formaldehyde, and their mixtures has been carried out. The processes of photooxidation of formaldehyde, phenol and their mixtures in an aqueous medium under the individual and combined eff ects of ultraviolet radiation and titanyl sulfate have been studied. The high effi ciency (up to 90%) of photocatalytic post-treatment of wastewater containing phenol and formaldehyde has been determined. It has been established that ultraviolet water treatment under static conditions can signifi cantly reduce the concentrations of phenol and formaldehyde to the values of the discharge standard into the city water canal. It has been proven that the introduction of titanyl sulfate microadditives (homogeneous photocatalytic process) makes it possible to intensify the oxidation process, while the addition of titanium(IV) compounds, due to its chemical inertness, will not have a toxic eff ect on the activated sludge biocenosis. Possible intermediate products of photooxidative degradation of phenol and formaldehyde are qualitatively determined. The kinetic dependences of the oxidation of phenol, formaldehyde and their mixtures are obtained, which allow further scaling up the process of photodegradation with the introduction of homogeneous catalysts for industrial facilities into the system. The proposed post-treatment method is included in the Best Available Techniques directory and will improve environmental and industrial safety.